PENGARUH KEDISIPLINAN TERHADAP KINERJA PEGAWAI PADA DINAS PENDIDIKAN DAN KEBUDAYAAN KABUPATEN SOPPENG - Rahmawati, Rahmawati; Parawangi, Anwar; Harakan, Ahmad (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2023)
This study aims to determine the effect of discipline on employee performance at the Office of Education and Culture of Soppeng Regency. This type of research is quantitative with a descriptive type of research which seeks to describe . Sources of data used are primary and secondary data. Primary data, namely the staff of the Office of Education and Culture of Soppeng Regency, collected 57 employees. While secondary data in the form of documentation and questionnaires. Data analysis techniques used in this quantitative research are validity test, reliability test, simple linear regression test, and hypothesis. The results of this study indicate that the regression results (influence) of Variable X on Variable Y simultaneously are 0.246 or 24.6%, meaning that the influence of discipline on the performance of employees in the office is low. While the effect of the variable Discipline (X) on employee performance (Y) partially shows the results per indicator that have an effect of no more than 0.277 or 27.7%, it shows discipline on the performance of low-level employees. So thus the effect of discipline in improving employee performance is low.